Legal Aspects of PPP Contracts in The Provision of Drinking Water in Gresik District - Darwati, Yulin; Kurniawan, Faisal; Thalib, Prawitra (CV. Ridwan Publisher, 2021)
The availability of drinking water is an essential legal issue in life. However, the government budget is limited in funding the infrastructure sector. Government policy on drinking water supply in the capital Gresik through the Public-private partnership (PPP) program. The purpose of this study is to provide background information and considerations for the Government to improve the basic and complete legal rules for PPP contracts for drinking water infrastructure in the capital. Gresik. This study uses empirical legal research methods, namely legal research related to the adoption or implementation of legal norms in force for each specific legal event that occurs. in society. The results of this study include (1) legal aspects of the implementation of the right to provide drinking water to residents of the Gresik Regency; (2) Due to budget constraints, and the Government can establish a public-private partnership in the field of Clean Water Supply; (3) The Government can provide regulatory guarantees for drinking water infrastructure projects through the Gresik District PPP program. The results of this study provide recommendations to the Government to ensure better implementation of the Gresik Regency's right to public drinking water